Go down, Moses the miscegenation of time - Kinney, Arthur F. 1933-2021 (Twayne's masterwork studies, 1996)
Go Down, Moses is one of William Faulkner's most direct and powerful assessments of race relations in America. In this compelling study, Arthur F. Kinney asserts that it is also his most personal - and perhaps most important - novel. Composed of seven complete stories spanning several generations in Faulkner's fictitious Yoknapatawpha County, Mississippi, the book's structure is deceptively simple. Indeed, Faulkner's publisher incorrectly printed the first edition with the title Go Down, Moses and Other Stories, until Faulkner insisted that the work be treated as a novel. Together, the stories' multiple viewpoints create a complex mosaic of the McCaslin family, whose white and mulatto branches are the product of several defining instances of miscegenation